Impact of physical exercise on short physical performance battery as the performance indicator of elderly in community setting: A meta-analysis of randomized controlled trials - Syafiqul Umam, Mohammad; Mardya Rakhmadhan, Iraky; Soenarti, Sri (Heart Science Journal, 2025)
BACKGROUND: Age-related physical decline affects daily activities and increases health risks in the elderly. Tailored exercise programs are essential for improving functional well-being, necessitating robust evaluations to confirm their efficacy. OBJECTIVES: The aim of this study is to present a comprehensive review of the influence of physical activity on the Short Physical Performance Battery (SPPB) as a performance metric within the elderly population. METHODS: In April 2024, an extensive investigation was carried out by reviewing literature obtained from reputable databases like PUBMED and COCHRANE. The study focused on interventions related to physical exercise for older adults, with a specific emphasis on utilizing the SPPB to gauge their effects on physical functionality. RESULTS: The analysis of six selected papers revealed a positive enhancement in performance following interventions that involved physical exercise. These interventions fell into three main categories: Vivifrail-based exercise, group-based exercise, and telemedicine-guided exercise. The statistical analysis indicated significant improvements (95% CI: 0.2861 to 0.9077; p Egger: 0.973, Q(5) = 156.3870, p < 0.0001, tau² = 0.1423, I² = 96.8826%). CONCLUSION: In conclusion, the findings suggest that tailored physical training regimes have the potential to improve physical capabilities among the elderly cohort. This highlights the importance of integrating such exercise routines into their daily schedules to promote overall health and functional performance.